Constructing intervertebral disc degeneration animal model: A review of current models - Liang, Tongzhou; Gao, Bo; Zhou, Jinlang; Qiu, Xianjian; Qiu, Jincheng; Chen, Taiqiu; Liang, Yanfang; Gao, Wenjie; Qiu, Xuemei; Lin, Youxi (Frontiers in Surgery, 2023)
Low back pain is one of the top disorders that leads to disability and affects disability-adjusted life years (DALY) globally. Intervertebral disc degeneration (IDD) and subsequent discogenic pain composed major causes of low back pain. Recent studies have identified several important risk factors contributing to IDD's development, such as inflammation, mechanical imbalance, and aging. Based on these etiology findings, three categories of animal models for inducing IDD are developed: the damage-induced model, the mechanical model, and the spontaneous model. These models are essential measures in studying the natural history of IDD and finding the possible therapeutic target against IDD. In this review, we will discuss the technical details of these models, the duration between model establishment, the occurrence of observable degeneration, and the potential in different study ranges. In promoting future research for IDD, each animal model should examine its concordance with natural IDD pathogenesis in humans. We hope this review can enhance the understanding and proper use of multiple animal models, which may attract more attention to this disease and contribute to translation research.